2009
DOI: 10.1021/jp8095709
|View full text |Cite
|
Sign up to set email alerts
|

High Level ab Initio Energies and Structures for the Rotamers of 1,3-Butadiene

Abstract: High level ab initio calculations, utilizing coupled cluster theory with quasi-perturbative triple excitations and augmented quadruple zeta level basis sets, have been used to determine the structures and relative energies of the four stationary points on the 1,3-butadiene torsional potential curve. Corrections were applied in order to minimize the residual basis set error, as well as account for core/valence correlation and scalar relativistic effects. Higher order correlation recovery was also included to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
99
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(117 citation statements)
references
References 53 publications
14
99
0
4
Order By: Relevance
“…The Role of the AGP Ansatz on the Electronic Correlation of 1,3-Butadiene. To make a comparison between our VMC structures and that obtained through CCSD(T)/CBS, 10 it is essential to clarify the stability of the VMC results. For this purpose, we have done different calculations with the basis sets described in Table 1, and with the atomic JAGP and the molecular JSD ansaẗze described in the Computational Methods.…”
Section: Resultsmentioning
confidence: 99%
“…The Role of the AGP Ansatz on the Electronic Correlation of 1,3-Butadiene. To make a comparison between our VMC structures and that obtained through CCSD(T)/CBS, 10 it is essential to clarify the stability of the VMC results. For this purpose, we have done different calculations with the basis sets described in Table 1, and with the atomic JAGP and the molecular JSD ansaẗze described in the Computational Methods.…”
Section: Resultsmentioning
confidence: 99%
“…(Note that bigger CASSCF active spaces [46] and highly correlated methods [47] have suggested that the planar C 2v BD geometry is unstable with respect to deformation of the central bond backbone dihedral and that the local minimum corresponds to a distorted structure. As the differences in electronic character between electronic states are more marked in the symmetric geometry and can be given a symmetry label, we will consider a C 2v initial BD structure as the FC geometry.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27] Thea dvent of modern electronic structure methods [28][29][30] and careful examination of gas-phase Raman spectra [31] have led to the prevailing view that cisbutadiene is in fact gauche. [32][33][34][35] Despite this progress, conclusive detection and structural characterization of this elementary molecule have remained elusive for sixty years. [36,37] Herein we report the first microwave spectrum of "cis" butadiene,w hich unambiguously shows that it possesses an onplanar gauche structure.T he experimental evidence for non-planarity,w hich includes not only an early complete equilibrium structure but also vivid observation of tunneling between equivalent gauche minima, was acquired with ac ombination of sensitive microwave techniques and high accuracy ab initio calculations.Examination of the structures and energetics obtained from both experiment and theory reveals detailed information about how the interplay of steric and conjugation effects determines the structure of this fundamental reaction intermediate.…”
mentioning
confidence: 99%